Examining hypoglycemia risk with systemic fluoroquinolone use: A systematic review and meta-analysis - Irene Jiayu Guo; Mira Maximos; John-Michael Gamble (CMI Communications)
Background: Hypoglycemia associated with fluoroquinolone use has been observed in several case reports and observational studies. Study Design: Systematic review and meta-analysis. Methods: Two independent reviewers screened studies identified from a literature search conducted using PubMed (Medline), Cochrane Library, and Ovid Embase databases from inception to June 24, 2024. Eligible studies included randomized controlled trials (RCTs), cohort studies, and case-control studies that reported quantitative findings regarding hypoglycemia and had a non-fluoroquinolone antimicrobial comparator. Random effects models were used to estimate pooled odds ratios (ORs) and 95 % confidence intervals (CIs) for the occurrence of hypoglycemia in people prescribed fluoroquinolones (at a class and individual agent level) versus active comparators for RCTs and observational studies. Subgroup analysis by diabetes status, concurrent use of hypoglycemic agents, renal impairment, and age were conducted. Results: There were 1771 citations screened of which 21 studies (9 RCTs and 12 observational) were included. Compared to other antimicrobials, fluoroquinolones were associated with an overall significantly increased risk of hypoglycemia across the RCTs (9 studies, Pooled OR = 1.84; 95 % CI 1.05–3.21; I2 = 0 %). Findings from observational studies showed an increased risk of hypoglycemia with gatifloxacin (5 studies, Pooled OR = 2.87; 95 % CI 1.65–4.99; I2 = 65 %) and levofloxacin (7 studies, Pooled OR = 1.90; 95 % CI 1.46–2.47; I2 = 75 %), but not with ciprofloxacin (6 studies, Pooled OR = 1.24; 95 % CI 0.97–1.59; I2 = 76 %) nor moxifloxacin (5 studies, Pooled OR = 1.28; 95 % CI 0.83–1.97; I2 = 67 %) compared to non-fluoroquinolone antimicrobials. Limitations: Inconsistencies in the definition of hypoglycemia, heterogeneity between observational studies, and hypoglycemia was not a primary outcome in any RCTs. Conclusion: The results of this systematic review and meta-analysis showed a significant association between fluoroquinolones and an increased risk of hypoglycemia, although there appears to be intraclass variation. As hypoglycemia is a serious adverse drug event associated with cognitive and cardiovascular complications, fluoroquinolones should be prescribed cautiously, particularly when safer antibiotic alternatives are available.